(untitled) (Academicia Globe: Inderscience Research, 2021)
This article examines the effectiveness of this system in foster care - infants - children - adolescents and graduates - people, as well as their future destiny. In addition, the current problems of the system have been studied in detail. Conditions for optimizing the process of social development of orphans and children left without parental care in orphanages, and the theoretical and scientific-methodological basis of the process of optimizing the formation of the personality of an orphan in a preschool orphanage have been developed and substantiated.